PENGARUH CURRENT RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON EQUITY PADA PT TIGARAKSA SATRIA Tbk PERIODE 2014-2023 - Nabila, Salwa; Mardiana, Sri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The purpose of this study is to determine the effect of Current Ratio and Total Asset Turnover on Return On Equity at PT Tigaraksa Satria Tbk, both partially and simultaneously. The research method used in quantitative method with associative approach. Data analysis in this study uses classical assumption test, multiple linear regression analysis, hypothesis, test and coefficient of determination test. The results of this study are multiple linear regression equation of Y=-14.467 + 9.580 X1 + 5.737 X2 + ?. Partially, the Current Ratio variable has a positive and significant effect on Return On Equity with the results of tcount > ttabel or (5,577 > 2,364) with a significant level of 0,001 < 0,05. While the Total Asset Turnover variable has a positive and significant influence on Return On Equity with the results of tcount > ttabel or (4,769 > 2,364) with a significant level of 0,002 < 0,05. Simultaneously Current Ratio and Total Asset Turnover have a positive and significant influence on Return On Equity with a value of fcount > ftable, namely (27,688 > 4,74) with a significance of 0,000 < 0,05. The coefficient of determination is 88,8%, the remaining 11,2% influenced by other variables and factors.